Preconception Counseling: Identifying Ways to Improve Services - Khyla Burrows; Jeanelle Sheeder; Virginia Lijewski; Teresa Harper (Thieme Medical Publishers, Inc., 2022)
Objective The aim of this retrospective study was to evaluate the maternal conditions for which preconception services are provided and the routine services and recommendations offered through the Maternal Fetal Medicine group at the University of Colorado (CU). The study sought to determine how services and recommendations differ by maternal condition, demographics, and reproductive health history. Materials and Methods Charts of patients who received preconception counseling through the CU MFM department during 2018 were reviewed to evaluate maternal conditions and the type of counseling patients received. Patients were grouped by their referral reason and subsequently by counseling recommendations to either proceed with immediate conception, defer immediate conception pending completion of further recommendations or to not conceive. Results Of the fifty-nine patients referred to preconception counseling, 52% (n = 31) of the women were referred for maternal disease, 40% (n = 24) for infertility, 32% (n = 19) for previous poor obstetric outcomes, 30% (n = 18) for advanced maternal age and finally, 15% (n = 9) for gynecologic anatomic abnormalities. Conclusion During the initial evaluation, 58% (n = 34) of patients were determined to have no concern for immediate conception while 7% (n = 4) were ultimately advised to not conceive. Using this data, we identified areas of preconception counseling that standardization will improve by ensuring patients receive comparable services and advice.